Genetic diversity in natural populations of (Cephalotaxus mannii Hook. F.) In Tay Nguyen, Vietnam base on SSR markers - Phòng, Đinh Thị; Liễu, Trần Thị; Hiền, Vũ Thị Thu (Vietnam Journal of Biotechnology, 2016)
Cephalotaxus mannii Hook.f. is one of 15 species of conifer in the Central Highlands. Cephalotaxus mannii is a scarce medicinal conifer endemic to the south central region of China and Vietnam. In Vietnam, although widely distributed species (Lao Cai, Ha Giang, Thanh Hoa, Nghe An, Thua Thien Hue, Kon Tum, Gia Lai, Lam Dong...) but is considered rare and vulnerable by the indiscriminately exploitation of people. In this study, 18 SSR markers were used to analyze the genetic diversity of 34 individuals C. mannii collected in Ta Nung and Hiep An of Lam Dong province. The results showed 12/18 polymorphic markers. Among 36 DNA amplified fragments, 24 were polymorphic (66.66%). Genetic diversity in Hiep An population (h = 0.269; I = 0.449 and PPB = 72.22%) was higher than that of Ta Nung (h = 0.433; I = 0.264 and PPB = 66.67%). The total level of molecular variance (AMOVA) among populations was 27.74% and among individuals within the populations was 72.26%. The average of gene flow value (Nm) of the species C. mannii populations was 3,310. Both Ta Nung and Hiep An populations had Wright’s inbreeding coefficient Fis <0 (- 0.244, - 0.052, respectively) and the private allele (Ap) (0.222, 0.333, respectively). A dendrogram constructed based on similarity matrix of 34 C. mannii samples divided into two main groups with their genetic similarity coefficient ranged from 65% (Cpm31 and Cpm32) to 100% (Cpm16 and Cpm17, Cpm21 and Cpm22). Molecular analysis results showed that C. mannii species should be protected at the population level.